Conservation of Marine Biological Diversity and Genetic Resources in Areas beyond National Jurisdiction as Common Heritage of Mankind - Zakieh Taghizadeh; Mahdi Haddadi (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2020)
Sustainable development of the oceans and regulating the seas by the application of the rule of law is considered as one of the most recent phenomena in the field of international law of the sea. Because of the exacerbated challenges and threats posed on the marine environment and the growing decline in genetic resources due to the expansion of human activities, the international community’s concerns about occurring environmental crises for future generations and the threat posed on the principles of intergenerational equity and the common heritage of mankind have been increasing. Therefore, the conservation and sustainable exploitation of marine biodiversity and genetic resources in areas beyond national jurisdiction in recent years have attracted the attention of the UN General Assembly. Therefore, it seems necessary that the legal regime governing biodiversity to be set out by a legally binding instrument under the Convention on the Law of the Sea (UNCLOS) through the consensus of all states. The following research, while outlining the international legal regime governing marine biodiversity, examines the legal effects and outputs arising out of the implementation of the doctrine of the common heritage of mankind on marine genetic resources in areas beyond national jurisdiction.